Groundwater and Global Change in the Western Mediterranean Area (Environmental Earth Sciences,, 2018)
This book is a compilation of papers examining the impacts of global change (GC) on water resources systems. Mainly focusing on groundwater resources in Western Mediterranean countries, it shows that this topic is one of the most important challenges facing society. The papers explore developments in both Southern Europe and North Africa, where major impacts on the sustainability, quantity, quality, and management of water resources are expected to emerge. Although most global change publications focus on surface water, the number of research papers addressing global change and groundwater has grown rapidly in recent years. Continuing that welcome trend, this book gathers the main findings presented at the "Congress on Groundwater and Global Change in the Western Mediterranean" (Granada, Spain, November 6-9, 2017), which brought together researchers and technicians interested in groundwater issues affecting this geographic area.